1998
DOI: 10.1126/science.280.5360.62
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Chondrules: Petrologic Tests of the Shock Wave Model

Abstract: Chondrules are millimeter-sized rounded igneous rocks within chondritic meteorites. Their textures and fractionated mineral chemistries suggest that they formed by repeated, localized, brief (minutes to hours) melting of cold aggregates of mineral dust in the protoplanetary nebula. Astrophysical models of chondrule formation have been unable to explain the petrologically diverse nature of chondrites. However, a nebular shock wave model for chondrule formation agrees with many of the observed petrologic and geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
113
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 19 publications
2
113
0
Order By: Relevance
“…First suggested by Wood (1963), gas dynamic shock waves in a low-temperature nebula are currently considered to be a plausible mechanism for providing the repetitive transient heating events that were apparently responsible for chondrule formation (Connolly and Love 1998;Jones et al 2000;Desch et al 2005). In support of this mechanism, it has been demonstrated that the shock wave model can simulate inferred chondrule thermal histories (heating rates, peak temperatures, cooling rates) for at least a limited range of input nebular and particle parameters (Desch and Connolly 2002;Ciesla and Hood 2002;Ciesla et al 2004b;Iida et al 2001;Hood et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…First suggested by Wood (1963), gas dynamic shock waves in a low-temperature nebula are currently considered to be a plausible mechanism for providing the repetitive transient heating events that were apparently responsible for chondrule formation (Connolly and Love 1998;Jones et al 2000;Desch et al 2005). In support of this mechanism, it has been demonstrated that the shock wave model can simulate inferred chondrule thermal histories (heating rates, peak temperatures, cooling rates) for at least a limited range of input nebular and particle parameters (Desch and Connolly 2002;Ciesla and Hood 2002;Ciesla et al 2004b;Iida et al 2001;Hood et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A successful theory of chondrule formation should at least meet the following constraints: (1) the extremely short heating timescale of roughly seconds to minutes (Connolly & Love 1998), (2) the cooling rate of 10 2 -10 3 K hr À1 (Radomsky & Hewins 1990;Lofgren & Lanier 1990), and (3) the narrow range of sizes (0.1-1 mm) inferred from laboratory analyses of textures and compositions as well as from attempts to reproduce chondrules. In addition, many chondrules show evidence of multiple heating events, so the heating event must have occurred more than once.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous models have been proposed to explain the formation of chondrules; however, none can yet be reconciled with the highly diverse mineralogical, chemical, and isotopic properties of these objects (e,g., Boss, 1996a). Arguably, the most successful models of chondrule formation suggest that chondrules form by the melting of preexisting dust particles by gas-drag heating in shock waves propagating through the solar nebula (Boss, 1996a,b;Connolly and Love, 1998). These theories predict many of the properties of chondrules and are also compatible with current models on the generation of shock waves (Connolly and Love, 1998).…”
Section: Introductionmentioning
confidence: 76%